(untitled) (Journal of Organizational Psychology, 2020)
Science, technology, engineering, and math (STEM) academic departments are expected to promote cutting-edge education supported by rapidly changing curriculum. Despite perceptions and assumptions for embracing innovation, funding agencies continue to target major educational reform in STEM disciplines, suggesting a lack of success. Research suggests difficulty in implementing curriculum change may be due to a non-innovative organizational culture. We examined whether the organizational culture of STEM academic departments is less change-oriented than assumed, which might explain the constant need for overhauling curriculum. Findings have implications for future funding decisions, STEM departments, and pedagogy in the discipline.